CHARACTERISTICS OF SOME PROMISING WILD SPECIES OF ESSENTIAL OIL PLANTS IN KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article discusses promising wild species of essential oil plants growing in themountainous areas of Kyrgyzstan. The place of growth, the content of essential oils and its usein official and folk medicine are given. This information may be useful to those interested in collecting medicinal plants. Hundreds of species of medicinal and essential oil plants are consideredpromising, of which not all species have been studied, and the species mentioned in the articlefound in the natural conditions of the republic have already been included in the State Pharmacopoeia. Based on the analysis of literary sources and data from the laboratory of medicinal andessential oil plants of the Institute, the content of essential oil was identified and the place wherethis species grows was given. The studies carried out on the presence of wild essential oil plantsin the flora of Kyrgyzstan are not final and, of course, require additional clarification and in-depthcomprehensive study of each species.
Keywords: wild species, medicinal and essential oil plants, essential oils, place of growth.